The incidence of allergic diseases in a pediatric practice in Turkey - Özkaragöz, Kemâl; Pırnar, Aysel; Karadeli, Fethi (The Turkish Journal of Pediatrics, 1963)
An investigation of the incidence of allergy among 1,096 pediatric patients seen at Hacettepe Children’s Hospital is presented. The patients were selected on a random basis, and represent about one-third of those brought to the clinic for treatment, or one-twentieth of the children treated all year. The presence or absence of allergic diseases was determined by the patient’s record, family history, physical examination, laboratory findings, response to treatment, and Rapaport’s allergic index technique. In this group of 1,096 children, 117 had one or more allergic syndromes. Only children with unquestionable major allergies were included in the study. The group is analyzed according to the type and incidence of allergy, and the age of onset of the allergic symptoms. This study is a pilot project undertaken at Hacettepe Medical Center, and further investigation into the incidence of allergic diseases in Turkey is being carried out.